2021
DOI: 10.5194/hess-2021-625
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the links between sub-seasonal clustering of extreme precipitation and high discharge in Switzerland and Europe

Abstract: Abstract. River discharge is impacted by the sub-seasonal (weekly to monthly) temporal structure of precipitation. One example is the successive occurrence of extreme precipitation events over sub-seasonal timescales, referred to as temporal clustering. Its potential effects on discharge have received little attention. Here, we address this question by analysing discharge observations following extreme precipitation events either clustered in time or occurring in isolation. We rely on two sets of precipitation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Milly et al (2005) showed that streamflow trends world wide are and will continue to be significantly impacted by changes in climatic factors. Studies show the impact of distribution and concentration of rainfall events on peaks of discharge Q (Tuel et al, 2022). However rivers are also highly managed and human activities are a main driver of change in the functioning of watersheds.…”
Section: Introductionmentioning
confidence: 99%
“…Milly et al (2005) showed that streamflow trends world wide are and will continue to be significantly impacted by changes in climatic factors. Studies show the impact of distribution and concentration of rainfall events on peaks of discharge Q (Tuel et al, 2022). However rivers are also highly managed and human activities are a main driver of change in the functioning of watersheds.…”
Section: Introductionmentioning
confidence: 99%
“…the impact of storms and flood quantified in WMO, 2021). Additionally, if several extreme precipitation events occur in close succession (temporal clustering), flooding becomes more likely Tuel et al (2022). The successful mitigation of weather-related hazards depends on our ability to forecast them reliably.…”
mentioning
confidence: 99%